Espacios de ciudad y estilos de vida. El espacio público y sus apropiaciones (2008)
ABSTRACT: Public spaces we frequent for leisure, exercising, recreation and everyday displacement raise important issues concerning the physical space vs. social space relationship, in which intra-personal and socio-cultural and physical-environmental reasoning and logics intervene. The right to experience the city and to enjoy an environmental quality become a necessary aspect to consider when it comes to promoting social inclusion and active lifestyles, as deterioration, invasion and/or shortage of city spaces -mainly public spaces- challenge the space appropriation, use and enjoyment. This poses significant challenges both to urban planning and health, sport and recreation policy-making. Therefore, we intend to value urban space on an experiential and personal appropriation basis, rather than on the architectural functionality aspect. That is, from what experiences and space appropriation can propitiate, and from their potential to be incorporated by the subject as a sensitive being, space articulated to the social group inhabiting it.